Transient thermal behaviors of a scaled turbine valve: Conjugate heat transfer simulation and experimental measurement. (October 2019) - Li, Fuqi; Quay, Bryan; Wang, Peng; Santavicca, Domenic A.; Wang, Weizhe; Xu, Sihua; Liu, Yingzheng
Highlights: Conjugate heat transfer simulation of a scaled turbine valve was performed. A high-temperature experiment test of unsteady temperature served as validation. Overall numerical errors using shear stress transport model were below 8%. Unsteady flow behaviors were shown to significantly enhance heat transfer. Non-uniform heat transfer in circumferential direction was well explained. Abstract: A conjugate heat transfer simulation of transient turbulent flow in a scaled turbine valve, which usually occurs in the fast start-up processes of coal-fired power plants, was performed against experimental validation. A high-temperature (615 °C) experimental system with a scaled (1:3) turbine valve was set up at Pennsylvania State University. Eighty thermocouples were flush-mounted in streamwise and circumferential directions inside the valve body, and spatio-temporally varying temperature and temperature gradients were acquired as the mainstream temperature and pressure rapidly varied. A simulation using the shear stress transport model showed considerably better agreement with the measured temperature than the standard k - ε model and the Realizable k - ε model; the numerical errors in valve top, valve chamber, valve seat and valve diffuser were below 1%, 2%, 5% and 8%, respectively. However, the largest errors located in the upper diffuser were confirmed to be associated with alternating oscillations of the annular attachment jet along the diffuser surfaces. Further investigations of transient thermal behaviors demonstrated that the instability of large-scale vortical structures inside the valve diffuser significantly enhanced heat transfer between the valve body and the air flow. In addition, upstream straighteners enabled the formation of separated secondary flow structures inside the diffuser, resulting in non-uniform heat transfer along the valve's circumferential direction.